Preliminary design for simultaneous saccharification and fermentation stages for ethanol production from sugar cane bagasse - Albernas Carvajal, Yailet (2017)
The interest of ethanol production from agro-industry residues as raw material has deserved great attention since these feedstocks may constitute an alternative to fossil fuels as well as represent beneficial effects both from economic and environmental point of view. The sugar cane bagasse (SCB) represents an available and cheap opportunity of raw material. The use of lignocellulosic biomass as a feedstock needs a pretreatment stage to breakdown lignocellulosic complex into lignin, cellulose and hemicelluloses, then the hydrolysis stage converts cellulose into fermentable glucose, and finally, in order to increase the glucose yield, simultaneous saccharification and fermentation (SSF) process is carried out. In this work a preliminary design for these stages is proposed. A mixed integer linear programming model is formulated in order to obtain the optimal number of parallel units in each stage and their sizes (plant configuration and capacity). The production planning along the time horizon of one year is determined, given by the number of batches to be processed and its size. Different production scenarios are analyzed, for which the investment cost is minimized, and economic profitability indicators are calculated.